Work-based learning in Europe : practices and policy pointers - (:unkn) unknown (My University, 2013)
"This policy handbook is one of the European Commission contributions to strengthen work-based learning (WBL) in initial vocational education and training (IVET) and is a follow-up to the mandate of the Bruges Communiqué to develop a 'vademecum/study on successful work-based learning models'. The aim of the Commission was to produce policy guidance illustrated by concrete practices from the Member States which can be used by policymakers and practioners to introduce or reinforce workbased learning elements in vocational education and training (VET). The document focuses on WBL in initial vocational training and this work will be complemented by Cedefop's review of work-based learning approaches in continuing vocational education and training (CVET) and research on the effectiveness of various forms of work-based learning in CVET. As 50 percent of young people in Europe at upper secondary level are enrolled in VET, the document focuses mainly on upper secondary VET." (Excerpt, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 1.5 Weiterbildung; I 2.2 Europa; Berufsausbildung; Weiterbildung; Lernen am Arbeitsplatz; Europa